Validity of zakat ratios as Islamic performance indicators in Islamic banking: A congeneric model and confirmatory factor analysis - Naji Mansour Nomran; Razali Bin Haron (ISRA International Journal of Islamic Finance, 2022)
Purpose - This paper considers zakat (Islamic tax) as an alternative indicator to measure the performance of Islamic banks (IBs). It aims to examine whether zakat ratios can be used as Islamic performance (ISPER) indicators for IBs besides the conventional performance (COPER) indicators. Design/methodology/approach - The investigation covered a sample of 214 yearly observations of 37 IBs located in Indonesia, Malaysia, Bahrain, Saudi Arabia and the United Arab Emirates for the period 2007-2015. This study used a single-factor congeneric model and confirmatory factor analysis, performed using the AMOS 23.0 software. Findings - The findings assert that the discriminant validity of multi-bank performance, as measured by ISPER [zakat on assets (ZOA) and zakat on equity (ZOE)] and COPER indicators (return on assets, return on equity and operational efficiency in terms of assets), is very high. Hence, ISPER and COPER measurements are valid, either together to measure the multi-performance of IBs from both the Islamic and conventional perspectives, or independently as each measurement is valid to measure the Islamic and conventional performance if it is used separately. Research limitations/implications - This paper does not investigate whether the findings are constant across time. This represents one of the limitations of this study. Practical implications - It is strongly recommended that IBs calculate and disclose zakat ratios, particularly ZOA and ZOE, in their annual reports. Researchers and academicians should use these ratios for measuring the ISPER of IBs, either along with COPER or separately. Originality/value - Empirical evidence is provided in this paper on the development and validity of zakat ratios as ISPER indicators in the Islamic banking industry. Zakat ratios are suitable indicators that can measure IBs' performance and achieve the goals of IBs as well as those of Islamic economics.
Keywords: 330; Confirmatory factor analysis; Islamic banks; Islamic performance measurement; Single-factor congeneric model; Zakat ratios